2001
DOI: 10.2105/ajph.91.5.761
|View full text |Cite
|
Sign up to set email alerts
|

Depression and substance use in minority middle-school students

Abstract: OBJECTIVES: This study investigated the association between depression and substance use in a sample of middle-school students. METHODS: The 5721 students (59%-63% Hispanic) completed self-report items on depressive symptoms, recent smoking and binge drinking, and lifetime use of marijuana, cocaine, and inhalants. RESULTS: Symptoms of depression were strongly and positively related to substance use. For every type of use, a stepwise increase was seen between the percentage of students with low symptom frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…As in other studies, 28 internalizing disorders and substance use were strongly associated (p<.001). Sixty percent of the control-group children who reported using substances also reported having internalizing disorders in the borderline/clinical range; and among those with internalizing disorders, the rate of substance use was 5 times higher (11%) than among those without internalizing disorders (2%).…”
Section: Discussionsupporting
confidence: 85%
“…As in other studies, 28 internalizing disorders and substance use were strongly associated (p<.001). Sixty percent of the control-group children who reported using substances also reported having internalizing disorders in the borderline/clinical range; and among those with internalizing disorders, the rate of substance use was 5 times higher (11%) than among those without internalizing disorders (2%).…”
Section: Discussionsupporting
confidence: 85%
“…As might be expected, boys were most likely to be represented in the higher lifetime-use groups as well as children in the eighth grade. The strength of grade rather than age differences suggest contextual changes may be important in understanding the significant shifts in drinking onset and progression to heavy use during middle school (Guilamo-Ramos et al, 2005; Kelder et al, 2001). Interestingly, being African American predicted current drinking behavior (average, heavy episodic, maximum drinks).…”
Section: Discussionmentioning
confidence: 99%
“…However, extreme caution should be used in interpreting these results as the number of African-American students within this sample of current drinkers was quite small ( N =30) and reflect students living within a restricted geographic area. Research examining ethnic differences in drinking among a large sample of middle school students ( N =5,721) found that African-American students were engaging in binge drinking at rates higher than any other racial or ethnic group (Kelder et al, 2001). Recent work suggests that racial/ethnic differences, such as being African American, should be considered in combination with other moderators (e.g., gender, self-esteem) when considering heavy episodic drinking in middle school (Patrick & Schulenberg, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to emotionally self-regulate is compromised when healthy attachment bonds are disrupted, which is common among children who are abused and no longer live with their biological parents (Racusin, Maerlender, Sengupta, Isquith & Straus, 2005). In the absence of sufficient internal resources, adolescents may use unhealthy methods to cope with these problems (Spaccarelli, 1994), such as using substances to self-medicate or alleviate distressing symptoms (Kelder et al, 2001). These maladaptive coping responses may increase adolescents’ risk for a range of risky behaviors, such as unprotected sex and other HIV risk behaviors.…”
mentioning
confidence: 99%